The role of microRNAs in atopic dermatitis - Mahsa Khosrojerdi; Farahzad Jabbari Azad; Yaser Yadegari; Hamid Ahanchian; Amir Azimian (Non-coding RNA Research)
Atopic dermatitis (AD), known as eczema, is a chronic inflammatory skin condition affecting millions worldwide. This abstract provides an overview of the clinical features and underlying pathogenesis of AD, highlighting the role of specific microRNAs (miRNAs) in its development and progression. AD presents with distinct clinical manifestations that evolve with age, starting in infancy with dry, itchy skin and red patches, which can lead to sleep disturbances. In childhood, the rash spreads to flexural areas, resulting in lichenification. In adulthood, lesions may localize to specific areas, including the hands and eyelids. Pruritus (itchiness) is a hallmark symptom, often leading to excoriations and increased vulnerability to skin infections. The pathogenesis of AD is multifaceted, involving genetic, immunological, and environmental factors. Skin barrier dysfunction, immune dysregulation, genetic predisposition, microbiome alterations, and environmental triggers contribute to its development. Recent research has uncovered the role of miRNAs, such as miR-10a-5p, miR-29b, miR-124, miR-143, miR-146a-5p, miR-151a, miR-155, and miR-223, in AD pathogenesis. These microRNAs play crucial roles in regulating various aspects of immune responses, keratinocyte dynamics, and inflammation. MicroRNA-10a-5p orchestrates keratinocyte proliferation and differentiation, while miR-29b regulates keratinocyte apoptosis and barrier integrity. MicroRNA-124 exhibits anti-inflammatory effects by targeting the NF-κB signaling pathway. MicroRNANA-143 counters allergic inflammation by modulating IL-13 signaling. MicroRNA-146a-5p regulates immune responses and correlates with IgE levels in AD. MicroRNA-151a shows diagnostic potential and modulates IL-12 receptor β2. MicroRNA-155 plays a central role in immune responses and Th17 cell differentiation, offering diagnostic and therapeutic potential. MicroRNA-223 is linked to prenatal smoke exposure and immune modulation in AD. Understanding these microRNAs' intricate roles in AD pathogenesis promises more effective treatments, personalized approaches, and enhanced diagnostic tools. Further research into these molecular orchestrators may transform the landscape of AD management, improving the quality of life for affected individuals.